RESEARCH OF ARC FURNACE ELECTRICAL MODE WITH A FUZZY CONTROL MODEL - Y. S. Paranchuk (National Technical University "Kharkiv Polytechnic Institute", 2020)
Goal. The purpose of the paper is to increase the efficiency of arc steelmaking furnace (ASF) operating modes control basing on the improvement of arc lengths control model. Method. The control model is based on the fuzzy set theory, and the structural modelling methodology is used to study the dynamics indices. Results. The structural scheme of a furnace arc lengths fuzzy control system and the electrical mode (EM) coordinate control dynamics parameters values in response to the deterministic and random arc lengths fluctuations were obtained. Scientific novelty. For the first time, a fuzzy model of an EM mismatch signal generation with operational adaptation to its current state in each phase was developed, which enabled by-phase independent control of arc lengths and improved energy efficiency. Practical value. Dynamic accuracy of EM coordinates stabilization at the setpoint level is improved, in particular the arc currents dispersion is reduced, which leads to a corresponding power loss decrease in arc furnace short network, an increase of the furnace productivity, as well as to an improvement of the electromagnetic compatibility of the arc furnace and power supply network.